Efficacy of Immune Checkpoint Inhibitors in Non-small-cell Lung Cancer Patients With Different Metastatic Sites: A Systematic Review and Meta-Analysis - Yang, Kaili; Li, Jiarui; Bai, Chunmei; Sun, Zhao; Zhao, Lin (Frontiers in Oncology, 2020)
Background: Organ-specific response patterns reported in previous studies indicate different response towards immune checkpoint inhibitors (ICIs) in non-small-cell lung cancer (NSCLC) patients with different metastatic sites. This study aims to compare the efficacy of ICIs with conventional therapy in NSCLC patients with bone, brain or liver metastases. Materials and Methods: MEDLINE, Embase and CENTRAL were searched for studies comparing ICIs with conventional therapy in NSCLC patients with bone, brain or liver metastases. The pooled hazard ratio (HR) of overall survival (OS) and progression-free survival (PFS) among included studies was analyzed using the random effects model. Results: Eight studies consisting of 988 NSCLC patients were included, 259 with brain metastases and 729 with liver metastases. No available study with bone metastases information was identified. For patients with brain metastases, ICIs significantly improved their OS (HR, 0.57; 95%CI, 0.37-0.86; P = 0.007). For patients with liver metastases, both OS (HR, 0.72; 95%CI, 0.57-0.91; P = 0.006) and PFS (HR, 0.72; 95%CI, 0.49-0.87; P = 0.004) improvements were observed in the ICI treatment arm. Subgroup analysis was conducted based on target of ICIs and treatment regimen. PD-1 inhibitors could benefit patients on OS and PFS regardless of metastatic sites, while PD-L1 inhibitors could not. Patients with brain metastases could only gain OS improvement from ICIs combined with chemotherapy, but for patients with liver metastases, the benefit was detected using ICIs single agent or ICIs combined with chemotherapy plus anti-VEGF therapy. Conclusion: ICIs could significantly improve OS in NSCLC patients with brain or liver metastases compared with conventional therapy. Although brain and liver metastases are generally considered as poor prognostic factors for immunotherapy, this study still indicates ICIs are effective therapeutic options for NSCLC patients with these metastatic sites.